Kajian Hukum Mengenai Prosedur Penanganan Barang Bukti Tindak Pidana Korupsi Oleh Kejaksaan Sebelum Dilimpahkan Ke Rupbasan - Riawindo Asay Sormin; Ediwarman Ediwarman; Taufik Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This article or paper aims to review and analyze the legal rules governing the handling of evidence of corruption by the prosecutor's office before being transferred to (Rupbasan), as well as the role of the prosecutor in handling evidence of corruption and policies carried out by the prosecutor in handling evidence of acts of crime. corruption crime. The problem is focused on how the rule of law and the role and policies of the Attorney General's Office in managing evidence. In order to approach this problem, legal systems theory, role theory and policy theory are used as references. The research method in this writing is a normative legal research method. Data were collected through primary, secondary and tertiary data sources, then analyzed using qualitative analysis methods. This study concludes that the legal regulations regarding the handling of evidence of criminal acts of corruption are: Minister of Law and Human Rights Regulation No. 16 of 2014, Regulation of the Chief of the National Police of the Republic of Indonesia No. 8 of 2014, Presidential Instruction No. 2 of 2014, Regulation of the Attorney General of the Republic of Indonesia No: PER-027 / A / JA / 10/2014. The role of the prosecutor in handling evidence, namely: The role of subsection of evidence and the role of subsection of loot. The policies implemented by the prosecutor regarding the handling of evidence include: Policies before being transferred to the state confiscated objects storage house and policies carried out by the Attorney after the court verdict.